Teknologi Produksi Dan Analisis Kelayakan Usahatani Benih Padi Di Provinsi Sulawesi Tengah - Syafruddin, Syafruddin; Padang, Irwan Suluk; Muchtar, Muchtar; Wahyuni, Andi Nirma; Suwitra, I Ketut; Rahayu, Heni SP; Saidah, Saidah (Politeknik Negeri Lampung., 2023)
Seed is an important component in increasing crop production and productivity. The availability of superior seeds of lowland rice nationally, including Central Sulawesi Province, is still very limited so that it becomes an obstacle in supporting the achievement of rice production. For this reason, an assessment of the seed supply model in the form of farmer groups is expected to be an alternative way to provide superior and quality rice seeds according to the wishes and preferences of farmers and available according to time. The research was carried out in three centers of lowland rice whose farmer groups have not been facilitated by the Department of Agriculture, both district and provincial. This study aims to 1. Determine the problem of fulfilling seeds at the field level and 2. To obtain a model of the seed production system at the level of farmers and farmer groups for the fulfillment of superior and quality seeds appropriately. The implementation of the activity consists of two stages: the first stage is the identification and characterization of seed potential and constraints and the second stage is the assessment of innovation and seed production technology at the level of breeder farmers and farmer groups. The results showed that farmers did not know about new high-yielding varieties including the procedures and requirements for plants to become seeds and difficulties in obtaining information related to seeds, so farmers planted existing varieties or expected for seed assistance. Yields and seed production at the three activity locations showed quite high yields, reaching 4.2 – 5.1 tons of seed/ha where in one ha production for seeds can supply seeds covering an area of ​​100 – 120 ha and can increase profits 2 to 3 times compared to grain production. In addition, the farmer group scale captive system can see the appearance of the plants that will be used as seeds